Clonal distribution of invasive pneumococci, Czech Republic, 1996-2003 - Zemlickova, Helena; Urbaskova, Pavla; Jakubu, Vladislav; Motlova, Jitka; Musilek, Martin; Prochazka, Bohumir (Emerging infectious diseases, 2010)
We conducted surveillance on invasive pneumococci isolated from adults in the Czech Republic during 1996-2003. The 7 most prevalent serotypes were characterized. Coverage with the 7-valent pneumococcal conjugate vaccine was low. Our observations confirm that detection methods may have modified the expected effect of this vaccine.
Keywords: Young Adult; Genotype; mladý dospělý; Adolescent; Česká republika; Adult; Aged; dospělí; senioři; mladiství; Czech Republic; Meningitis, Pneumococcal; lidé; Humans; Serotyping; pneumokoková meningitida; bakteriemie; sérotypizace; Streptococcus pneumoniae; Bacteremia; genotyp; lidé středního věku; Middle Aged